Untangling with Value Stream Mapping : how to use VSM to address behavioral and cultural patterns and quantify waste in multifunctional and nonrepetitive work environments - Contras, Ovidiu ([Place of publication not identified] : Productivity Press, 2022)
The standard belief in books about Lean initiatives and value stream mapping (VSM) is that VSM works well on transactional processes (which are primarily linear processes where handoffs are well defined and the outcome is known) and it is useful for repetitive projects or products. This book counters these statements by clearly demonstrating how a VSM exercise can be successfully performed in complex, multifunctional environments involving nonrepetitive work, such as aircraft new product development, custom engineering, software development and project management.
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics; Production planning; Value analysis (Cost control); BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Workplace Culture